Pani Dalloway - Woolf, Virginia, 1882-1941.; Tarnowska, Krystyna (Krakow : Wydawn. Znak, 2003)
Polish translation of "Mrs. Dalloway". As Clarissa Dalloway prepares for an elaborate party, she remembers another summer in the past, when she was a beautiful young woman. Her preparations are interrupted by the unexpected arrival of a former suitor from that long-ago summer. As the day of the party unfolds, Mrs. Dalloway's life also becomes strangely intertwined with a young man she never meets, but whose tragic fate strikes a chord of truth, deep in her soul, that she cannot deny.
Translation of: Mrs. Dalloway.
Keywords: Married women -- England -- Fiction; London (England) -- Fiction; Middle class women -- England -- Fiction